Inhibition of Water Channels by HgCl(2) in Intact Wheat Root Cells - Zhang, Wen-Hao (American Society of Plant Physiologists, 1999)
To assess the extent of water flow through channels in the membranes of intact higher plant cells, the effects of HgCl(2) on hydraulic conductivity (L(P)) of wheat (Triticum aestivum L.) root cells were investigated using a pressure probe. The L(P) of root cells was reduced by 75% in the presence of 100 μm HgCl(2). The K(+)-channel blocker tetraethylammonium had no effect on the L(P) at concentrations that normally block K(+) channels. HgCl(2) rapidly depolarized the membrane potential (V(m)) of the root cells. The dose-response relationship of inhibition of L(P) and depolarization of V(m) were not significantly different, with half-maximal inhibition occurring at 4.6 and 7.8 μm, respectively. The inhibition of L(P) and the depolarization of V(m) caused by HgCl(2) were partially reversed by β-mercaptoethanol. The inhibition of L(P) by HgCl(2) was similar in magnitude to that caused by hypoxia, and the addition of HgCl(2) to hypoxia-treated cells did not result in further inhibition. We compared the L(P) of intact cells with that predicted from a model of cortical cells incorporating water flow across both the plasma membrane and the tonoplast using measured values of water permeability from isolated membranes, and found that HgCl(2) has other effects in addition to the direct inhibition of water channels.